2022
DOI: 10.1002/emp2.12655
|View full text |Cite
|
Sign up to set email alerts
|

Thirty‐day mortality with andexanet alfa compared with prothrombin complex concentrate therapy for life‐threatening direct oral anticoagulant‐related bleeding

Abstract: Objective Compare 30‐day mortality among patients receiving the specific reversal agent andexanet alfa versus replacement prothrombin complex concentrate (PCC) in the management of direct‐acting oral anticoagulant (DOAC)–related bleeds. Methods Two patient‐level datasets were used: ANNEXA‐4, a prospective, single‐arm trial of patients taking apixaban or rivaroxaban who received andexanet alfa and ORANGE, a prospective, observational study of anticoagulated patients in U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 39 publications
2
22
0
3
Order By: Relevance
“…The results of our analysis are generally consistent with prior, considerably smaller, comparative case series [23][24][25]. Barra and colleagues [26] reported a case series of apixaban-or rivaroxaban-associated intracranial hemorrhage patients managed with andexanet alfa (n = 18) or 4F-PCC (n = 11).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The results of our analysis are generally consistent with prior, considerably smaller, comparative case series [23][24][25]. Barra and colleagues [26] reported a case series of apixaban-or rivaroxaban-associated intracranial hemorrhage patients managed with andexanet alfa (n = 18) or 4F-PCC (n = 11).…”
Section: Discussionsupporting
confidence: 88%
“…The results of this analysis also align with other indirect comparison studies for andexanet alfa versus usual care-treated patients with FXa inhibitor bleeding in the UK and Germany. Cohen and colleagues compared propensity score (model based on age, bleed location, history of atrial fibrillation, venous thromboembolism, stroke, renal dysfunction, and cancer)-adjusted cohorts of andexanet alfa-and PCC-managed FXa inhibitor major bleeding patients [24]. As in our study, the andexanet alfa cohort was derived from ANNEXA-4, while a synthetic control arm of PCC patients was drawn from the prospective, observational ORANGE study (which assessed the presentation and clinical outcomes of major bleeding episodes associated with oral anticoagulant use in the UK between October 2013 and August 2016) [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bislang wurden indirekte Kohortenanalysen publiziert, welche die ANNEXA-4-Patienten mit nationalen Registern (RETRACE II, ORANGE) vergleichen, in denen Patienten mit PCC/4 F-PCC behandelt wurden. Sie gelangen zu sehr heterogenen Ergebnissen hinsichtlich klinischer Outcome-Parameter und Komplikationsraten [13,14]. Dies gilt ebenso für unterschiedliche Dosierungsstrategien für PCC/4F-PCC.…”
Section: Dabigatranunclassified
“…A recent propensity score-matched analysis showed that the adjusted 30day mortality rates were lower for patients treated with andexanet alfa than in matched patients receiving PCC. 20 Further studies comparing these two drugs on different outcomes are necessary to reach a final conclusion. The recommendation regarding the use of idarucizumab for dabigatran reversal in an ongoing haemorrhage is surprisingly restrained.…”
mentioning
confidence: 99%